Do head-restraints protect the neck from whiplash injuries?. Issue 1 (March 1989) - Morris, F
Abstract : Over an 11-month period a study was made of all patients presenting to an accident and emergency department who had sustained whiplash as a result of rear-bumper impacts. The patients were analysed with respect to the presence of head-restraints in their vehicles. A significant increase in the incidence of whiplash was found in patients whose vehicles did not have head-restraints fitted. Legislation requiring all passenger cars to have head-restraints fitted as standard would have a major impact in reducing the number of whiplash injuries sustained in rear bumper impacts.